The Impact of Islamic International Law on Contemporary Global Conflicts - Aftab Haider (Qiyam Islamic Studies Center Foundation, 2025)
The integration of Islamic International Law (IIL) with modern global legal systems presents significant challenges, particularly in addressing issues of sovereignty, human rights, and conflict resolution. As global conflicts and international relations evolve, there is a need for legal frameworks that incorporate diverse traditions, including IIL, to ensure justice, fairness, and peace. This article highlights the growing relevance of IIL, exploring its potential role in addressing contemporary global challenges such as climate change, economic justice, and conflict resolution. The objectives of this study are to examine the historical foundations of IIL, assess its current relevance, and explore the possibilities for harmonizing IIL with modern international legal norms. Despite its historical influence, IIL remains underexplored in addressing global challenges, particularly in the context of international treaties, human rights, and the evolving global order. The methodology employs a comparative analysis of IIL principles with contemporary international law, supported by case studies like the Iran Nuclear Deal and Saudi Arabia's intervention in Yemen. The findings indicate that Islamic International Law (IIL) significantly shapes the dynamics of contemporary global conflicts by providing alternative frameworks for conflict resolution, promoting justice-oriented diplomatic practices, and influencing the legal approaches of Muslim-majority states in issues such as humanitarian intervention, human rights, and treaty negotiations. The implications of this study advocate for greater dialogue between Islamic legal traditions and global legal systems, suggesting that a balanced approach could enhance global governance and provide practical solutions for issues such as peace-building, climate action, and human rights protection.